NON INAVSIVE BIOSENSOR FOR DIABETES MONITORING - Yadav, Lokendra (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective-A method and apparatus to detect blood glucose non invasively by measuring the vaporÂ exhaled by humans, whichÂ usually consisting of Â numerous volatile organic compounds (e.g. acetone, ethanol, isoprene) generated in the liver, mainly from the oxidation of fatty acids, which further are exported to peripheral tissues. Method- The proposed measurement system is based on the concentration of the gases present in exhaled breath Detection is completely non-invasive and non-contact type based on metal oxide gas sensors. The developed device will provide non-invasive diagnosis, monitoring of pathological processes and assessment of pharmacological response. Results- The proposed method could perfectly detect traces of Volatile organic compounds (VOC's), when introduced with the fraction of milliliter of gas (sample) Conclusion- The present sensor grid is suitable to produce results on Â some fraction of milliliter quantity of gas. Such compound when detected for the case of diabetes and asthma will indicate the presence of disease. Since we didn't had any opportunity to conduct a test on human being. It is presumed that the system will work satisfactorily for detection of such diseases in non-invasive manner. Key words: Volatile organic compound, Diabetes, Metal oxide biosensors, Non-invasive Sensors, Diagnosis, Pharmacological respons